Xenophobic discrimination - Atrey, S (Wiley, 2023)
This article presents a general account of xenophobic discrimination in international law. It shows that the dominant grounds-based approach to addressing xenophobic discrimination as either (i) racial discrimination or (ii) discrimination based on nationality or citizenship, fails to capture what is wrong about xenophobic discrimination. Likewise, the suggestion to address xenophobic discrimination via a dedicated ground like foreignness may also fail given the inherently intersectional character of foreignness as in turn constituted by other grounds. Instead, xenophobic discrimination can be understood as a sui generis category of discrimination which is not necessarily based on a particular ground, but which leads to the particular harm of disbelongingness or civic ostracisation which excludes people from participating in the social, political, economic and cultural life of the communities they find themselves in. The article thus makes three contributions: first, it proposes a shift away from a grounds-based to a harm-based approach to discrimination in international law; secondly, it delineates the nature of harm entailed in xenophobic discrimination; and thirdly, it shows why such harm should be treated as prima facie wrongful in international law.